Reliability Evaluation of Low-voltage Switchgear Based on Maximum Entropy Principle - Zhang Zhigang; Wang Jingqin; Wang Li; Wang Meng (Universitas Ahmad Dahlan, 2017)
In this paper, based on the definition of two-parameter joint entropy and the maximum entropy principle, a method was proposed to determine the prior distribution by using the maximum entropy method in the reliability evaluation of low-voltage switchgear. The maximum entropy method takes kinds of priori information as different constraints. The optimal prior distribution was selected by maximizing entropy under these constraints, which not only contains the known prior information but also tries to avoid the introduction of other assumption information. Based on non-parametric bootstrap method, the hyper-parameters of prior distribution is obtained by two-order moment of prior information. Finally, with the bootstrap method, the prior distribution robustness and the posterior robustness were analyzed, and the posterior mean time between failures for the low-voltage switchgear was estimated.